Stanje i mogućnosti uključivanja saobraćaja BiH u evropski saobraćajni sistem - Kulović, Mirsad (Promet - Traffic&Transportation, 2012)
This paper deals with the reached traffic/ transport development level in Bosnia and Herzegovina with a brief reference to the state in individual traffic aspects, and then the assessment is provided of the possibilities of integration of traffic in Bosnia and Herzegovina into the EC traffic system, while emphasizing as priority activities to be taken the granting of conditions for a uniform and standardized treatment of all traffic aspects/segments, rendering usable the traffic infrastructure facilities and advancement of technology, engineering and management of transport.